2004
DOI: 10.1038/labinvest.3700057
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of autocrine motility factor in metastatic tumor cells: possible association with augmented expression of KIF3A and GDI-β

Abstract: Autocrine motility factor (AMF), which is identical to phosphohexose isomerase (PHI)/glucose-6-phosphate isomerase (GPI) , a ubiquitous enzyme essential for glycolysis, neuroleukin (NLK), a neurotrophic growth factor, and maturation factor (MF) mediating the differentiation of human myeloid cells, enhances the motility and metastatic ability of tumor cells. AMF/PHI activity is elevated in the serum or urine in patients with malignant tumors. Here, we constructed an amf/phi/nlk/mf gene using adenovirus vector a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 49 publications
(45 reference statements)
1
38
0
Order By: Relevance
“…A larger number of genes thought to be associated with tumorigenesis have been shown to be overexpressed in TOVs in our microarray analysis. These include GPI whose expression correlates with increased motility and metastatic activity of tumor cells (Yanagawa et al, 2004) and whose overexpression in ovarian tumors has previously been reported (Lee et al, 2004).…”
Section: Discussionmentioning
confidence: 82%
“…A larger number of genes thought to be associated with tumorigenesis have been shown to be overexpressed in TOVs in our microarray analysis. These include GPI whose expression correlates with increased motility and metastatic activity of tumor cells (Yanagawa et al, 2004) and whose overexpression in ovarian tumors has previously been reported (Lee et al, 2004).…”
Section: Discussionmentioning
confidence: 82%
“…After 24 hours, the phagokinetic tracks were visualized using dark-field illumination under a Nikon inverted microscope. The area cleared of gold particles by at least 50 cells was measured using NIH image 1.62, and the standard error reflecting the 95% confidence level was calculated 39) .…”
Section: Methodsmentioning
confidence: 99%
“…To find the proteins interacting with PGI/AMF, cDNA library screening was done using the CytoTrap two-hybrid system (Stratagene) according to the instruction manual. Briefly, mouse pgi/amf gene that had been generated as previously reported (18) was inserted into pSos vector to produce human son of sevenless (hSos) protein fused with mouse PGI/AMF, which was used as a bait protein. cDNA library originated from mouse smooth muscle and inserted into pMyr vector that contains DNA encoding the myristylation membrane localization signal (Myr) was also purchased from Stratagene.…”
Section: Methodsmentioning
confidence: 99%
“…The signaling pathways downstream of AMFR include protein kinase CK2 (17), Rho family regulators, the rho GDP dissociation inhibitor h, and kinesin motor 3A, and is implicated in epithelial-mesenchymal transition by down-regulation of Ecadherin expression through the up-regulation of its transcription suppressor (e.g., Snail; refs. 18,19). We cloned the human and the mouse gp78/AMFR genes that were found to encode a novel conserved seven-transmembrane protein harboring a RING-H2 motif and a leucine zipper motif (20).…”
Section: Introductionmentioning
confidence: 99%